Three-dimensional analysis of the trajectory of the ankle while running - Cunningham, T. J.; Uhl, T. L.; Shapiro, R.; Mattacola, C. G. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
The ankle is a possible attachment point between the lower extremity and a device which can guide the lower extremity through motions similar to running. There is a lack of published data to statistically support descriptions of the trajectories of the lower limb during running. The following research was conducted to provide additional detail and understanding to previous works studying ankle trajectories over several running speeds.